Macrophage-Derived Extracellular Vesicles as Carriers of Alarmins and Their Potential Involvement in Bone Homeostasis - Pieters, Bartijn C. H.; Cappariello, Alfredo; van den Bosch, Martijn H. J.; van Lent, Peter L. E. M.; Teti, Anna; van de Loo, Fons A. J. (Frontiers in Immunology, 2019)
Extracellular vesicles are a heterogeneous group of cell-derived membranous structures, which facilitate intercellular communication. Recent studies have highlighted the importance of extracellular vesicles in bone homeostasis, as mediators of crosstalk between different bone-resident cells. Osteoblasts and osteoclasts are capable of releasing various types of extracellular vesicles that promote both osteogenesis, as well as, osteoclastogenesis, maintaining bone homeostasis. However, the contribution of immune cell-derived extracellular vesicles in bone homeostasis remains largely unknown. Recent proteomic studies showed that alarmins are abundantly present in/on macrophage-derived EVs. In this review we will describe these alarmins in the context of bone matrix regulation and discuss the potential contribution macrophage-derived EVs may have in this process.